Energy Efficiency Of A Solar Green Building Using Bio-sourced Materials For Indoor Temperature And Humidity Optimization - Soumia Mounir; Youssef Maaloufa; Abdelhamid Khabbazi; Elina Mohd Husini; Nurul Syala Abdul Latip; Yakubu Aminu Dodo; Rime EL Harrouni; Mina Amazal; Asma Souidi; Malika Atigui; Ahmed Aharoune (Tech Science Press, 2025)
Indexed by Scopus/ERA